Relations of heart-type and brain-type fatty acid-binding proteins with postoperative cognitive dysfunction in elderly patients undergoing spinal surgery - Jiang,Minbo (2021)
SUMMARY OBJECTIVE: The aim of this study is to analyze the relations of heart-type fatty acid-binding protein (H-FABP) and brain-type fatty acid-binding protein (B-FABP) with postoperative cognitive dysfunction (POCD) in elderly patients undergoing spinal surgery. METHODS: One hundred and twenty-five patients who underwent spinal surgery were enrolled in this study. According to whether patients had POCD within 5 days after surgery, the participants were divided into POCD group and non-POCD group. Before surgery and 6 h after surgery, the serum H-FABP and B-FABP contents were detected. RESULTS: There were 33 (26.4%) patients in POCD group, and 92 (73.60%) patients in non-POCD group. After surgery, the serum H-FABP and B-FABP contents in POCD group were significantly higher than those before surgery, respectively (p<0.05), and those in non-POCD group were significantly lower than those before surgery, respectively (p<0.05). After surgery, the serum H-FABP and B-FABP contents in POCD group were significantly higher than those in non-POCD group, respectively (p<0.05). CONCLUSION: The serum H-FABP and B-FABP contents are positively related to the occurrence of POCD in elderly patients undergoing spinal surgery.